The case of Second Year Secondary School EFL Textbook 'Getting Through' Dissertation Submitted to the Faculty of Letters and Languages, Department of English, in Partial Fulfillment of the Requirements for the Degree of Master in Didactics of Foreign Languages - M'HAMDIA Hana (My University, 2022)
Abstract The present research is to invesitigate s the cultural content of the English textbook "Getting through” which is used in the Algerian secondary school. Schools it investigates the views of pupils and teachers of the second-year level about the importance of culture in EFL classes. This work is based on the hypothesis that learner have favorable attitudes about cultural materials, such as learning about the culture of the target language, they will be more interested in the Foreign Language context. To test the research hypothesis, a survey consisting of two questionnaires is carried out .The first questionnaire is directed to secondary school teachers of English to investigate whether they consider culture in the classroom or not and to get more knowledge about the materials they use to teach culture. The second questionnaire is designed for second year secondary school pupils so as to know about their perceptions of the place of culture in their English class. Also, results of the field work confirm the result of the analysis. In the light of these finding, a number of recommendations are suggested to teachers to adequately implement culture teaching in the classroom, and to pupils to make them aware about the cultural component in ForeignLanguage Learning.